Urgensi Ratifikasi Statuta Roma Bagi Indonesia - Danel Aditia Situngkir (UIR Law Review)
The presence of permanent the International Criminal Court is a realization of the efforts of the international community to provide protection against human rights from extraordinary crimes against humanity. The court established under the Rome Statute has been ratified by 123 countries. Indonesia is not a country which ratified the Rome Statute which came into force on 1 July 2002. The issues to be discussed in this paper are the jurisdiction of the International Criminal Court compared to the Indonesian Human Rights Court and the urgency of the roma statute in relation to sovereignty for Indonesia. The research method is done by normative juridical approach with data collection method through literature study which then analyzed as a legal issue to discuss urgency of ratification of roma statute for Indonesia. From the discussion it is concluded that the jurisdiction of the International Criminal Court is more complete than the Human Rights Court in Indonesia and the urgency of ratification of rome statute if associated with the sovereignty of the state should not be feared because the court only to complete as complementary principles in the statutes of Rome.